Asian Yearbook of International Law. - Yi, Sŏg-u, 1967-; Lee, Hee Eun (Brill; Nijhoff, 2023)
The Yearbook aims to promote research, studies and writings in the field of international law in Asia, as well as to provide an intellectual platform for the discussion and dissemination of Asian views and practices on contemporary international legal issues.